Bis(pentafluorophenyl)borane-catalyzed E-selective isomerization of terminal alkenes to internal alkenes. Issue 5 (30th January 2023) - Phatake, Ravindra S.; Müller, Tizian; Averdunk, Arthur; Gellrich, Urs
Abstract : The bis(pentafluorophenyl)borane-catalyzed E -selective isomerization of terminal alkenes to internal alkenes via a hydroboration/retro-hydroboration sequence is reported. Abstract : We report the bis(pentafluorophenyl)borane-catalyzed E -selective isomerization of terminal alkenes to internal alkenes. The reaction proceeds under comparatively mild conditions and requires only low catalyst loadings. Notably, a long-range isomerization of distant aryl alkenes is possible with the protocol reported herein. The mechanism was investigated by dispersion-corrected spin-component scaled double hybrid DFT computations, which indicate that the bis(pentafluorophenyl)borane catalyzed alkene isomerization proceeds via a hydroboration/retro-hydroboration sequence.